2015
DOI: 10.1055/s-0035-1556959
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcosis: A brief review

Abstract: Echinococcosis (hydatid disease) is the infection of humans by the larval stages of taeniid cestodes of the genus Echinococcus. Three species of public health importance, Echinococcus granulosus, E. multilocularis, and E. vogeli respectively, cause cystic, alveolar and polycystic echinococcosis respectively, and are the subject of this review. Several studies have shown that these diseases are an increasing public health concern and that both can be regarded as emerging or re-emerging diseases. In this review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In China, it belongs to the class II of animal epidemic. The first Chinese epidemiological survey of CE indicated that the prevalence range of disease is wide, the self-protection awareness of the crowd is poor, the propaganda and control power of disease is weak and the number of infected persons and the burden of social treatment ranked firstly in the world for China (3,4). E. g mainly parasitizes in the liver and lung and easily to form a cyst even endanger life, with high fatality rate (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In China, it belongs to the class II of animal epidemic. The first Chinese epidemiological survey of CE indicated that the prevalence range of disease is wide, the self-protection awareness of the crowd is poor, the propaganda and control power of disease is weak and the number of infected persons and the burden of social treatment ranked firstly in the world for China (3,4). E. g mainly parasitizes in the liver and lung and easily to form a cyst even endanger life, with high fatality rate (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Echinococcus granulosus sensu lato (E. granulosus s. l.) larval stage (metacestode) is the causative agent of Cystic Echinococcosis (CE), which is a zoonotic disease considered to be a re-emerging disease in several countries worldwide including Africa and Middle East (1) . CE causes great economic loss in livestock through condemnation of infected organs (mainly liver) and can be responsible for a life-threatening infection in humans (2) .…”
Section: Introductionmentioning
confidence: 99%